Peripheral Occipital Nerve Decompression Surgery in Migraine Headache. Issue 10 (October 2020) - Baldelli, Ilaria; Mangialardi, Maria Lucia; Salgarello, Marzia; Raposio, Edoardo
Abstract : Background: Migraine headache in the occipital region is characterized by a recurrent pain of moderate to severe intensity. However, the diagnosis can be difficult because of the multitude of symptoms overlapping with similar disorders and a pathophysiology that is not well-understood. For this reason, the medical management is often complex and ineffective. Methods: A literature search according to Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines was conducted to evaluate the surgical treatment of occipital migraines. Inclusion criteria were: English language, diagnosis of migraine, occipital neuralgia, or tension headache in compliance with the classification of the International Headache Society, follow-up at minimum 3 months, and adult age. The treatment had to consist of peripheral occipital nerve surgery. Results: 323 records were identified after duplicates were removed, 30 full text articles were assessed for eligibility, and 9 records were selected for inclusion. A total of 1046 patients were included in the review. General positive response after surgery (>50% reduction in occipital migraine headaches) ranged from 80.0% to 94.9%. However, many differences in the selection of patients, target of decompression surgery, and measurement outcome were described. Conclusion: Despite the decennial proven effectiveness and safeness of surgical therapy for chronic occipital migraine headaches, more significant proof is needed to definitively confirm its use as a standard therapy.